Seismic Diffraction Imaging to Characterize Mass‐Transport Complexes: Examples From the Gulf of Cadiz, South West Iberian Margin. Issue 3 (18th March 2021) - Ford, Jonathan; Urgeles, Roger; Camerlenghi, Angelo; Gràcia, Eulàlia
Abstract: Mass‐transport complexes (MTCs) are often characterized by small‐scale discontinuous internal structure, such as slide blocks, rough interfaces, faults, and truncated strata. Seismic images may not properly resolve such structure because seismic reflections are fundamentally limited in lateral resolution by the source bandwidth. The relatively weak seismic diffractions, instead, encode information on subwavelength‐scale structure, with superior illumination. In this paper, we compare diffraction imaging to conventional, full‐wavefield seismic imaging to characterize MTCs. We apply a seismic diffraction imaging workflow based on plane‐wave destruction filters to two 2D marine multichannel seismic profiles from the Gulf of Cadiz. We observe that MTCs generate a large amount of diffracted energy relative to the unfailed confining sediments. The diffraction images show that some of this energy is localized along existing discontinuities imaged by the full‐wavefield images. We demonstrate that, in combination with full‐wavefield images, diffraction images can be utilized to better discriminate the lateral extent of MTCs, particularly for thin bodies. We suggest that diffraction images may be a more physically correct alternative to commonly used seismic discontinuity attributes derived from full‐wavefield images. Finally, we outline an approach to utilize the out‐of‐plane diffractions generated by the 3D structure of MTCs, normally considered a nuisance in 2D seismic processing. We use a controlled synthetic test and a real‐data example to show that under certain conditions these out‐of‐plane diffractions might be used to constrain the minimum width of MTCs from single 2D seismic profiles. Plain Language Summary: Underwater landslides are a significant geohazard that can generate large magnitude tsunami and threaten seafloor infrastructure such as pipelines and telecommunication cables. The deposits from these events (so‐called mass‐transport complexes, or MTCs) can preserve internal structure that can reveal the dynamics of failure, important to understanding the geohazard potential of future events. One common tool for investigating these deposits is seismic imaging, which uses recordings of seismic waves reflected and scattered from the subsurface to image the geology. The resolution of the reflected waves, however, is often too poor to properly characterize the complex, strongly deformed internal structure of MTCs. In this study, we instead use the seismic waves scattered at lateral, basal, and internal discontinuities formed by landslide processes to produce diffraction images of MTCs. We show that these images have improved resolution and illumination of the small‐scale structure. We suggest that diffraction imaging could be a useful tool for geohazard investigations of complex geology. Key Points: Seismic diffractions encode information about the small‐scale internal structure of mass‐transport complexes (MTCs) Diffraction images offer a low‐cost route to improve the lateral resolution and effective vertical resolution of seismic images of MTCs 2D seismic profiles record out‐of‐plane diffractions generated by MTCs, which may be used to put minimum constraints on their 3D geometry